Dependência e Desenvolvimento na América Latina despois da Reforma do Estado - Pires, João (Cinta de Moebio. Revista de Epistemología de Ciencias Sociales, 2000)
This paper analizes the work of Fernando Henrique Cardoso and Enzo Faletto (Dependência e Desenvolvimento), to see the relation between state and social classes in the brazilian development process, yersteday and today.